Four-layer core-shell structure up-conversion luminescent material taking red light as main material and having greatly improved red light emission and preparation method of four-layer core-shell structure up-conversion luminescent material
By upconverting the luminescent material with a four-layer core-shell structure, the problems of cross relaxation and surface quenching when the red light emission is insufficient and the absorption cross-section of existing nanomaterials are solved, and the significant improvement of red light emission and the absorption cross-section are achieved.
Patent Information
- Application Number
- CN202411828305.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-25
AI Technical Summary
The red light emission of existing upconverted nanomaterials is insufficient, and it is difficult to reduce cross relaxation and surface quenching effects when increasing the absorption cross-section, which limits its application potential in the fields of biological imaging and other fields.
NaEr1-xF4:xTm@NaYbF4@NaYF4@NaYF4 upconverting the luminescent material with a four-layer core-shell structure, reducing the dissolution effect and surface defects of the sensitizer Yb3+ by adding high concentrations of Yb3+ ions between the luminescent center layer and the sensitizing layer, and by covering the inert shell layer in two times.
The red light emission intensity of the material is significantly improved, the absorption cross-section is increased, while the cross-relaxation and surface quenching effects are reduced, and the quantum efficiency of the material and the coverage of the bioimaging window are improved.
Smart Images

Figure HDA0005184911020000011 
Figure HDA0005184911020000021 
Figure HDA0005184911020000022
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano luminescent materials, and specifically relates to a four-layer core-shell structure upconversion luminescent material with mainly red light and greatly improved red light emission, and a preparation method thereof. Background Art
[0002] Upconversion nanomaterials can absorb multiple long-wavelength low-energy photons and then radiate short-wavelength high-energy photons. They have large anti-Stokes shift emission, can eliminate the autofluorescence generated by ultraviolet light excitation, have good biocompatibility and a large penetration depth under near-infrared excitation. These characteristics have made upconversion nanomaterials receive widespread attention in the research community. Upconversion nanoparticles based on lanthanide ions have shown a wide range of application prospects, including security, temperature sensing, display, solar cells, in vitro and in vivo imaging, and magnetic resonance imaging applications. Traditional upconversion nanomaterials such as NaYF4:18%Yb,2%Er@NaYF4 are mainly green light, and the wavelength is not in the biological imaging window, so the application is limited. Therefore, it is necessary to develop red light emitting upconversion nanomaterials with a greater penetration depth.
[0003] Upconversion nanomaterials are usually composed of a matrix, a sensitizer, and an activator, and their luminescence intensity is affected by factors such as cross relaxation, surface quenching, and absorption cross section. A larger specific surface area will cause a large number of surface defects, thereby exacerbating fluorescence quenching, so nanoparticles with a core-shell structure are usually used to improve the quantum efficiency and luminescence intensity of upconversion nanomaterials. Higher sensitizer and activator doping concentrations can increase the absorption cross section but will also intensify cross relaxation. Therefore, how to reduce cross relaxation and surface quenching while increasing the absorption cross section has become a problem worth studying. Wei Gao et al. doped 15% Yb in NaErF4 to obtain an 18K nanoparticle with a surface area of 150 nm. 3+ NaErF4:15% Yb was synthesized, which improved the absorption cross section of the material and greatly enhanced the red emission. Xiangshui Cui et al. doped 20% Yb in NaErF4 3+ Based on the doping of a small amount of Tm 3+ NaErF4:20%Yb,1%Tm was obtained, which made the material have a higher red-green ratio. Rashmi Joshi et al. coated NaErF4:0.5%Tm with 20%Yb 3+ The active shell of NaErF4:0.5%Tm@NaYF4:20%Yb was obtained, which reduced the cross relaxation by spatial separation of activator and sensitizer, further enhancing the red emission.
[0004] The NaEr of the present invention 1-XF4:xTm@NaYbF4@NaYF4@NaYF4, based on NaErF4:0.5%Tm@NaYF4:20%Yb, innovatively uses Yb 3+ The double-layer structure design of the luminescent center layer NaErF4 and the sensitizing layer NaYbF4 not only retains the spatial separation of the sensitizer and the activator, but also improves the sensitizing ion Yb 3+ The concentration of Yb was reduced, which reduced cross relaxation and increased the absorption cross section. In particular, we used the strategy of coating the inert shell twice to effectively reduce the concentration of Yb 3+ The dissolution effect isolates the excitation energy from passing through the high concentration Yb 3+ The pathway of migration to the surface of nanomaterials reduces the quenching effect caused by surface defects, significantly improving the red emission of the material. While increasing the absorption cross section of the transfer material, it solves the problem of fluorescence quenching caused by cross relaxation and surface quenching. Summary of the invention
[0005] In response to the problems existing in the prior art, the present invention provides a four-layer core-shell structure upconversion luminescent material with red light as the main emission and greatly improved red light emission, and a preparation method thereof, so as to expand its application potential in biological imaging and other aspects.
[0006] The technical solution of the present invention is as follows:
[0007] A four-layer core-shell structure upconversion luminescent material with red light as the main emission and greatly improved red light emission, the chemical formula is NaEr 1-x F4:xTm@NaYbF4@NaYF4@NaYF4, where x=0~2%.
[0008] Preferably, x=0.2-1.0%, particularly preferably x=0.5%; when x=0.5%, the red light intensity of the up-conversion luminescent material is 4.7 times greater than the red light intensity when x=0.
[0009] The luminescent core layer of the up-conversion luminescent material of the present invention is NaEr 1-x F4:xTm, the sensitizing layer is NaYbF4; the inert shell is double-layer NaYF4.
[0010] The up-conversion luminescent material of the present invention is a hexagonal crystal with a particle size of 20 to 25 nm.
[0011] The method for preparing the upconversion luminescent material of the present invention comprises the following steps:
[0012] S1. Preparation of luminescent core
[0013] Add ErCl3 and TmCl3 to a mixed solvent of oleic acid (OA) and 1-octadecene (ODE), react at 140-160°C for 30-60 minutes to obtain a rare earth oleic acid complex (Ln-OA), cool to room temperature, add a methanol solution of sodium oleate and NH4F, stir evenly and evaporate to remove methanol, then react at 290-310°C under inert gas protection for 60-90 minutes, cool to room temperature, add a precipitant, centrifuge and wash to obtain a luminescent core;
[0014] The molar ratio of ErCl3, TmCl3, sodium oleate and NH4F is 1-x:x:2.5:4, x=0-2%;
[0015] S2. Preparation of core-shell nanocrystals
[0016] YbCl3 is added to a mixed solvent of oleic acid and 1-octadecene, and the mixture is reacted at 140-160°C for 30-60 minutes to obtain a shell precursor solution, which is then cooled to room temperature, and the luminescent core prepared by S1 is added as a seed crystal, and a methanol solution of sodium oleate and NH4F is added, and the methanol is evaporated after being stirred evenly, and then the mixture is reacted at 290-300°C under the protection of an inert gas for 60-90 minutes, and then cooled to room temperature, a precipitant is added, and the mixture is centrifuged and washed to obtain core-shell structure nanocrystals;
[0017] The molar ratio of YbCl3, sodium oleate, and NH4F is 1:2.5:4;
[0018] S3. Inert Shell Coating
[0019] Add Y(CH3COO)3 to a mixed solvent of oleic acid and 1-octadecene, react at 140-160°C for 30-60 minutes to obtain a shell precursor solution, cool to room temperature, add the core-shell structure nanocrystals prepared by S2 as seed crystals, and add a methanol solution of sodium oleate and NH4F, stir evenly and evaporate to remove methanol, then react at 290-300°C under inert gas protection for 60-90 minutes, cool to room temperature, add a precipitant, centrifuge, wash, and complete an inert shell coating; repeat the coating operation once to obtain a four-layer core-shell structure upconversion luminescent material;
[0020] The molar ratio of Y(CH3COO)3, sodium oleate and NH4F is 1:2.5:4.
[0021] In the above preparation method,
[0022] The volume ratio of oleic acid to 1-octadecene is 6:14;
[0023] The concentration of NH4F methanol solution is 0.4 mol / L;
[0024] The specific operation of removing methanol by volatilization is as follows: first, the reaction solution is heated to 70-80°C to volatilize the methanol, and after the methanol is greatly reduced, the temperature is raised to 110-120°C for degassing to completely remove the methanol;
[0025] The specific operation of centrifugation and washing is as follows: after adding the precipitant to the reaction system, the precipitate is collected by centrifugation, dispersed in a non-polar solvent for ultrasonic washing, the precipitant is added for precipitation, the precipitate is collected by centrifugation, and dispersed in a non-polar solvent for standby use; the precipitant is methanol or ethanol; the non-polar solvent is cyclohexane or n-hexane; the centrifugation conditions are 8000r / min, 5min.
[0026] The principles of the present invention include:
[0027] Tm 3+ When the ions are doped into the core, they act as energy capture centers, converting Er 3+ The excitation photon energy is confined to the core region. 3+ The sensitizing shell of the ion significantly improves the absorption cross section and effectively transfers energy to the Er-rich 3+ core, spatially separated activators (Er 3+ ) and sensitizer (Yb 3+ ) can reduce the occurrence of cross relaxation, thereby inhibiting the rate of non-radiative channels. In addition, the secondary inert shell can not only reduce surface defects, but also reduce the dissolution of sensitizers, thereby effectively reducing surface quenching, which significantly improves the red emission of the material.
[0028] The beneficial effects of the present invention are:
[0029] The up-conversion nanomaterial of the present invention has a double-layer structure design of a luminescent center layer NaErF4 and a sensitizing layer NaYbF4, which not only retains the spatial separation of high-concentration sensitizers and activators, but also improves the sensitizing ion Yb 3+ The concentration of Yb was reduced, which reduced cross relaxation and increased the absorption cross section. 3+ The dissolution effect isolates the excitation energy from passing through the high concentration Yb 3+ The pathway for migration to the surface of nanomaterials reduces the quenching effect caused by surface defects and significantly enhances the red emission of the material.
[0030] The up-conversion nanomaterial of the present invention is activated by high concentration of Er 3+ At the same time, a small amount of Tm is doped 3+ , Tm 3+ Playing the role of energy capture center, Er is used to transfer energy in reverse. 3+The red light emission is significantly enhanced while the green emission is reduced, thus obtaining an upconversion nanomaterial with red light emission as the main component.
[0031] Compared with the existing methods, the present invention solves the fluorescence quenching problem caused by cross relaxation and surface quenching while increasing the absorption cross section of the upconversion material. The upconversion nanomaterial of the present invention is prepared by coprecipitation method, with a particle size of 20-25nm, uniform size, stable properties, and the main luminescence is located in the first biological imaging window (NIR-I), which has broad application prospects in the fields of biological labeling and imaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 : Up-conversion emission spectra of Examples 1-5.
[0033] Figure 2 : Comparison of up-conversion emission spectra of Example 2 (NaErF4: 0.5% Tm@NaYbF4@NaYF4@NaYF4) and Comparative Example 1 (NaYF4: 18% Yb, 2% Er@NaYF4).
[0034] Figure 3 : TEM image of NaErF4:0.5%Tm core in Example 2.
[0035] Figure 4 : TEM image of NaErF4:0.5%Tm@NaYbF4@NaYF4@NaYF4 in Example 2.
[0036] Figure 5 : Comparison of emission spectra of NaErF4:0.5%Tm@NaYbF4@NaYF4@NaYF4 and NaErF4:0.5%Tm cores in Example 2.
[0037] Figure 6 : Comparison of emission spectra of NaErF4:0.5%Tm@NaYbF4@NaYF4@NaYF4 and NaErF4:0.5%Tm@NaYbF4@NaYF4 in Example 2.
[0038] Figure 7 : Comparison of emission spectra of Example 2 (NaErF4: 0.5% Tm@NaYbF4@NaYF4@NaYF4) with Comparative Example 2 (NaErF4@NaYF4@NaYF4) and Comparative Example 3 (NaErF4: 0.5% Tm@NaYF4@NaYF4).
[0039] Figure 8: Comparison of emission spectra of Example 2 (NaErF4: 0.5% Tm@NaYbF4@NaYF4@NaYF4) and Comparative Example 4 (NaErF4: 0.5% Tm@NaYF4@NaYbF4: 0.2% Tm@NaYF4). DETAILED DESCRIPTION
[0040] The embodiments of the technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention and are therefore only used as examples and cannot be used to limit the protection scope of the present invention.
[0041] A four-layer core-shell structure upconversion nanomaterial, whose chemical formula is NaEr 1-x F4:xTm@NaYbF4@NaYF4@NaYF4. like Figure 1 As shown, after many experiments and comparisons, in the embodiment, x=0.5% is selected to achieve the characteristic that the red light is mainly red light and the red light is greatly improved. Figure 4 As shown, the material particle size is 20 to 25 nm, the size is uniform, and the dispersion is good.
[0042] Example 1: Preparation of NaErF4@NaYbF4@NaYF4@NaYF4 upconversion nanomaterials
[0043] Preparation of the core of upconversion nanoparticles: Add 1 mmol of ErCl3 to a mixed solvent of 6 ml of oleic acid (OA) and 14 ml of 1-octadecene (ODE), react at 150°C for 60 min to obtain a rare earth oleic acid complex (Ln-OA), cool, add 2.5 mmol of sodium oleate and 10 mL of a methanol solution containing 4 mmol of NH4F, stir well and heat to 80°C to volatilize the methanol, after most of the methanol is removed, heat to 120°C and degas for 15 min to completely remove the methanol, then heat to 290°C and react under inert gas protection for 60 min, add ethanol to the reacted solution and centrifuge at 8000 r / min for 5 min to obtain the core of the luminescent nanoparticles, disperse the precipitate in cyclohexane and fully sonicate, then add ethanol to precipitate it, centrifuge and wash again, and finally disperse the core in cyclohexane for standby use.
[0044] Coating active sensitizing layer: Using the core prepared in the above step as a seed, epitaxially grow the NaYbF4 shell layer by seed-mediated growth method.
[0045] 1 mmol of YbCl3 was added to a mixed solvent of 6 ml of oleic acid (OA) and 14 ml of 1-octadecene (ODE), and the mixture was reacted at 150 °C for 60 min to obtain a rare earth oleic acid complex (Ln-OA). After cooling, the luminescent nanoparticle core prepared in the previous step was added as a seed to the shell precursor solution, and then 2.5 mmol of sodium oleate and 10 mL of a methanol solution containing 4 mmol of NH4F were added. After being fully stirred, the mixture was heated to 80 °C to volatilize the methanol. After most of the methanol was removed, the mixture was heated to 120 °C and degassed for 15 min to completely remove the methanol. The mixture was then heated to 300 °C and reacted under inert gas protection for 90 min. Ethanol was added to the reacted solution and the mixture was centrifuged at 8000 r / min for 5 min to obtain a luminescent nanoparticle precipitate. The precipitate was dispersed in cyclohexane and fully sonicated. Then ethanol was added to precipitate the precipitate. The mixture was centrifuged and washed again. Finally, the material was dispersed in cyclohexane for standby use.
[0046] The first coating of the inert shell layer: the core-shell structure material prepared in the above step is used as a seed, and the NaYF4 shell layer is epitaxially grown by the seed-mediated growth method.
[0047] 1 mmol of Y(CH3COO)3 was added to a mixed solvent of 6 ml of oleic acid (OA) and 14 ml of 1-octadecene (ODE), and the mixture was reacted at 150°C for 60 min to obtain a rare earth oleic acid complex (Ln-OA). After cooling, the luminescent nanoparticles prepared in the previous step were added as seeds to the shell precursor solution, and 2.5 mmol of sodium oleate and 10 mL of a methanol solution containing 4 mmol of NH4F were added. The mixture was stirred well and then heated to 80°C to evaporate the methanol. After most of the methanol was removed, the mixture was heated to 120°C and degassed for 15 min to completely remove the methanol. The mixture was then heated to 290°C and reacted under inert gas protection for 90 min. Ethanol was added to the reacted solution and the mixture was centrifuged at 8000 r / min for 5 min to obtain a luminescent nanoparticle precipitate. The precipitate was dispersed in cyclohexane and fully sonicated. Ethanol was then added to precipitate the precipitate. The mixture was centrifuged and washed again. Finally, the material was dispersed in cyclohexane for standby use.
[0048] Second coating of the inert shell: Use the core-shell structure material prepared in the previous step as a seed to continue epitaxially growing the NaYF4 shell by the seed-mediated growth method.
[0049] 1 mmol of Y(CH3COO)3 was added to a mixed solvent of 6 ml of oleic acid (OA) and 14 ml of 1-octadecene (ODE), and the mixture was reacted at 150°C for 60 min to obtain a rare earth oleic acid complex (Ln-OA). After cooling, the luminescent nanoparticles prepared in the previous step were added as seeds to the shell precursor solution, and 2.5 mmol of sodium oleate and 10 mL of a methanol solution containing 4 mmol of NH4F were added. The mixture was stirred well and then heated to 80°C to evaporate the methanol. After most of the methanol was removed, the mixture was heated to 120°C and degassed for 15 min to completely remove the methanol. The mixture was then heated to 290°C and reacted under inert gas protection for 90 min. Ethanol was added to the reacted solution and the mixture was centrifuged at 8000 r / min for 5 min to obtain a luminescent nanoparticle precipitate. The precipitate was dispersed in cyclohexane and fully sonicated. Ethanol was then added to precipitate the precipitate. The mixture was centrifuged and washed again. Finally, the material was dispersed in cyclohexane for standby use.
[0050] Example 2: Preparation of NaErF4:0.5% Tm@NaYbF4@NaYF4@NaYF4 upconversion nanomaterials.
[0051] The difference between Example 2 and Example 1 is that the amount of ErCl3 added is reduced to 0.995 mmol when preparing the upconversion nanoparticle core, and 0.005 mmol TmCl3 is added at the same time to obtain a NaErF4: 0.5% Tm core. The remaining steps are the same as in Example 1.
[0052] Example 3: Preparation of NaErF4:1%Tm@NaYbF4@NaYF4@NaYF4 upconversion nanomaterials.
[0053] The difference between Example 3 and Example 1 is that the amount of ErCl3 added is reduced to 0.99 mmol when preparing the core of the upconversion nanoparticles, and 0.01 mmol TmCl3 is added at the same time to obtain a NaErF4:1% Tm core. The remaining steps are the same as in Example 1.
[0054] Example 4: Preparation of NaErF4:1.5%Tm@NaYbF4@NaYF4@NaYF4 upconversion nanomaterials.
[0055] The difference between Example 4 and Example 1 is that the amount of ErCl3 added is reduced to 0.985 mmol when preparing the upconversion nanoparticle core, and 0.015 mmol TmCl3 is added at the same time to obtain a NaErF4:1.5% Tm core. The remaining steps are the same as in Example 1.
[0056] Example 5: Preparation of NaErF4:2%Tm@NaYbF4@NaYF4@NaYF4 upconversion nanomaterials.
[0057] The difference between Example 5 and Example 1 is that the amount of ErCl3 added is reduced to 0.98 mmol when preparing the core of the upconversion nanoparticles, and 0.02 mmol TmCl3 is added at the same time to obtain a NaErF4:2% Tm core. The remaining steps are the same as in Example 1.
[0058] Comparative Example 1: Preparation of NaYF4:18%Yb,2%Er@NaYF4 upconversion nanomaterials.
[0059] Preparation of upconversion nanoparticle core: 0.8mmol Y(CH3COO)3, 0.18mmol Yb(CH3COO)3 and 0.02mmolEr(CH3COO)3 were added to a mixed solvent of 6ml oleic acid (OA) and 14ml 1-octadecene (ODE), and reacted at 150℃ for 60min to obtain rare earth oleic acid complex (Ln-OA). After cooling, 2.5mmol sodium oleate and 10mL methanol solution containing 4mmolNH4F were added, and the mixture was stirred well and heated to 80℃ to volatilize methanol. After most of the methanol was removed, the mixture was heated to 120℃ and degassed for 15min to completely remove the methanol. The mixture was then heated to 300℃ and reacted under inert gas protection for 90min. Ethanol was added to the reacted solution and centrifuged at 8000r / min for 5min to obtain the luminescent nanoparticle core. The precipitate was dispersed in cyclohexane and fully sonicated. Then ethanol was added to precipitate it. After centrifugation, the core was washed again. Finally, the core was dispersed in cyclohexane for standby use.
[0060] Coating the inert shell: Using the core prepared in the above step as a seed, epitaxially grow the NaYF4 shell by the seed-mediated growth method.
[0061] 1mmol of Y(CH3COO)3 was added to a mixed solvent of 6ml of oleic acid (OA) and 14ml of 1-octadecene (ODE), and the mixture was reacted at 150°C for 60min to obtain a rare earth oleic acid complex (Ln-OA). After cooling, the luminescent nanoparticle core prepared in the previous step was added as a seed to the shell precursor solution, and then 2.5mmol of sodium oleate and 10mL of a methanol solution containing 4mmol of NH4F were added. After being fully stirred, the mixture was heated to 80°C to volatilize the methanol. After most of the methanol was removed, the mixture was heated to 120°C and degassed for 15min to completely remove the methanol. The mixture was then heated to 290°C and reacted under inert gas protection for 90min. Ethanol was added to the reacted solution and the mixture was centrifuged at 8000r / min for 5min to obtain a luminescent nanoparticle precipitate. The precipitate was dispersed in cyclohexane and fully sonicated. Then ethanol was added to precipitate the precipitate. The mixture was centrifuged and washed again. Finally, the material was dispersed in cyclohexane for standby use.
[0062] Comparative Example 2: Preparation of NaErF4@NaYF4@NaYF4 upconversion nanomaterials.
[0063] Preparation of the core of upconversion nanoparticles: Add 1 mmol of ErCl3 to a mixed solvent of 6 ml of oleic acid (OA) and 14 ml of 1-octadecene (ODE), react at 150°C for 60 min to obtain a rare earth oleic acid complex (Ln-OA), cool, add 2.5 mmol of sodium oleate and 10 mL of a methanol solution containing 4 mmol of NH4F, stir well and heat to 80°C to volatilize the methanol, after most of the methanol is removed, heat to 120°C and degas for 15 min to completely remove the methanol, then heat to 290°C and react under inert gas protection for 60 min, add ethanol to the reacted solution and centrifuge at 8000 r / min for 5 min to obtain the core of the luminescent nanoparticles, disperse the precipitate in cyclohexane and fully sonicate, then add ethanol to precipitate it, centrifuge and wash again, and finally disperse the core in cyclohexane for standby use.
[0064] The first coating of the inert shell layer: the core structure material prepared in the above step is used as a seed to epitaxially grow the NaYF4 shell layer by a seed-mediated growth method.
[0065] 1 mmol of Y(CH3COO)3 was added to a mixed solvent of 6 ml of oleic acid (OA) and 14 ml of 1-octadecene (ODE), and the mixture was reacted at 150°C for 60 min to obtain a rare earth oleic acid complex (Ln-OA). After cooling, the luminescent nanoparticles prepared in the previous step were added as seeds to the shell precursor solution, and 2.5 mmol of sodium oleate and 10 mL of a methanol solution containing 4 mmol of NH4F were added. The mixture was stirred well and then heated to 80°C to evaporate the methanol. After most of the methanol was removed, the mixture was heated to 120°C and degassed for 15 min to completely remove the methanol. The mixture was then heated to 290°C and reacted under inert gas protection for 90 min. Ethanol was added to the reacted solution and the mixture was centrifuged at 8000 r / min for 5 min to obtain a luminescent nanoparticle precipitate. The precipitate was dispersed in cyclohexane and fully sonicated. Ethanol was then added to precipitate the precipitate. The mixture was centrifuged and washed again. Finally, the material was dispersed in cyclohexane for standby use.
[0066] Second coating of the inert shell: The core-shell structure material prepared in the previous step is used as a seed to continue epitaxially growing the NaYF4 shell by the seed-mediated growth method.
[0067] 1 mmol of Y(CH3COO)3 was added to a mixed solvent of 6 ml of oleic acid (OA) and 14 ml of 1-octadecene (ODE), and the mixture was reacted at 150°C for 60 min to obtain a rare earth oleic acid complex (Ln-OA). After cooling, the luminescent nanoparticles prepared in the previous step were added as seeds to the shell precursor solution, and 2.5 mmol of sodium oleate and 10 mL of a methanol solution containing 4 mmol of NH4F were added. The mixture was stirred well and then heated to 80°C to evaporate the methanol. After most of the methanol was removed, the mixture was heated to 120°C and degassed for 15 min to completely remove the methanol. The mixture was then heated to 290°C and reacted under inert gas protection for 90 min. Ethanol was added to the reacted solution and the mixture was centrifuged at 8000 r / min for 5 min to obtain a luminescent nanoparticle precipitate. The precipitate was dispersed in cyclohexane and fully sonicated. Ethanol was then added to precipitate the precipitate. The mixture was centrifuged and washed again. Finally, the material was dispersed in cyclohexane for standby use.
[0068] Comparative Example 3: Preparation of NaErF4:0.5% Tm@NaYF4@NaYF4 upconversion nanomaterials.
[0069] The difference between Comparative Example 3 and Comparative Example 2 is that the amount of ErCl3 added is reduced to 0.995 mmol when preparing the upconversion nanoparticle core, and 0.005 mmol TmCl3 is added at the same time to obtain a NaErF4: 0.5% Tm core. The remaining steps are the same as those of Comparative Example 2.
[0070] Comparative Example 4: Preparation of upconversion nanomaterials of NaErF4:0.5%Tm@NaYF4@NaYbF4:0.2%Tm@NaYF4.
[0071] The preparation method of the core of the upconversion nanoparticle and the coating method of the inert shell are the same as those of Comparative Example 3, except that a layer of NaYbF4:0.2%Tm shell is coated after the first coating of the inert shell, and then a second layer of the inert shell is coated. The coating method of the NaYbF4:0.2%Tm shell is as follows:
[0072] 0.998mmol YbCl3 and 0.002mmol TmCl3 were added to a mixed solvent of 6ml oleic acid (OA) and 14ml 1-octadecene (ODE), and reacted at 150℃ for 60min to obtain a rare earth oleic acid complex (Ln-OA). After cooling, the nanoparticles prepared in the previous step were added as seeds to the shell precursor solution, and 2.5mmol sodium oleate and 10mL methanol solution containing 4mmol NH4F were added. After fully stirring, the temperature was raised to 80℃ to volatilize the methanol. After most of the methanol was removed, the temperature was raised to 120℃ and degassed for 15min to completely remove the methanol. The temperature was then raised to 300℃ and reacted under inert gas protection for 90min. Ethanol was added to the reacted solution and centrifuged at 8000r / min for 5min to obtain a luminescent nanoparticle precipitate. The precipitate was dispersed in cyclohexane and fully ultrasonicated, and then ethanol was added to precipitate it. After centrifugation, it was washed again, and finally the material was dispersed in cyclohexane for standby use.
[0073] Depend on Figure 1 It can be seen that Example 2 of the present invention uses high Er doping 3+ At the same time, low Tm 3+ The method of spatial separation of high-concentration activators and sensitizers and double surface coating of inert shells successfully made NaErF4:0.5Tm@NaYbF4@NaYF4@NaYF4 an upconversion nanomaterial with red light as the main source and greatly improved red light. Compared with the nanomaterial without Tm 3+ The red light emission of doped Example 1 was increased by 4.7 times.
[0074] Depend on Figure 2 It can be seen that compared with the traditional NaYF4:18Yb,2Er@NaYF4 (Comparative Example 1), its red luminescence is increased by 26.5 times.
[0075] Depend on Figure 5 It can be seen that compared with NaErF4:0.5Tm with only a crystal core without a sensitizing layer and an inert shell layer, its red light emission is increased by 720 times.
[0076] Depend on Figure 6 It can be seen that the red light emission of the material obtained in Example 2 is increased by 2.8 times compared with NaErF4:0.5Tm@NaYbF4@NaYF4 which is only coated with an inert shell once.
[0077] Depend on Figure 7 It can be seen that compared with NaErF4@NaYF4@NaYF4 and NaErF4:0.5Tm@NaYF4@NaYF4 simply coated with an inert shell, its red light emission is increased by 198 times and 24.4 times respectively.
[0078] Depend on Figure 8It can be seen that sandwiching an inert layer between the active layer and the sensitizing layer will greatly increase the green emission of the material, while adding a small amount of Tm 3+ This will cause the material to have obvious blue-purple luminescence, and these characteristics do not meet the purpose of the present invention to improve the red-green ratio of the material.
[0079] Depend on Figure 3 , Figure 4 It can be seen that the core of the material is about 8nm, and after multiple coatings it is about 22nm, which is a smaller upconversion nanomaterial.
Claims
1. A four-layer core-shell structure upconversion luminescent material with red light as the main emission and greatly improved red light emission, the chemical formula is NaEr 1-x F4:xTm@NaYbF4@NaYF4@NaYF4, where x=0~2%.
2. The four-layer core-shell structure upconversion luminescent material with red light as the main component and greatly improved red light emission as claimed in claim 1, characterized in that: x=0.2~1.0%。 3. The method for preparing a four-layer core-shell structure upconversion luminescent material with red light as the main component and greatly improved red light emission as claimed in claim 1, characterized in that: The steps include: S1. Preparation of luminescent core Add ErCl3 and TmCl3 to a mixed solvent of oleic acid and 1-octadecene, react at 140-160°C for 30-60 minutes to obtain a rare earth oleic acid complex, cool to room temperature, add a methanol solution of sodium oleate and NH4F, stir evenly and evaporate to remove methanol, then react at 290-310°C under inert gas protection for 60-90 minutes, cool to room temperature, add a precipitant, centrifuge and wash to obtain a luminescent core; S2. Preparation of core-shell nanocrystals YbCl3 is added to a mixed solvent of oleic acid and 1-octadecene, and the mixture is reacted at 140-160°C for 30-60 minutes to obtain a shell precursor solution, which is then cooled to room temperature, and the luminescent core prepared by S1 is added as a seed crystal, and a methanol solution of sodium oleate and NH4F is added, and the methanol is evaporated after being stirred evenly, and then the mixture is reacted at 290-300°C under the protection of an inert gas for 60-90 minutes, and then cooled to room temperature, a precipitant is added, and the mixture is centrifuged and washed to obtain core-shell structure nanocrystals; S3. Inert Shell Coating Add Y(CH3COO)3 to a mixed solvent of oleic acid and 1-octadecene, react at 140-160°C for 30-60 minutes to obtain a shell precursor solution, cool to room temperature, add the core-shell structure nanocrystals prepared by S2 as seed crystals, and add a methanol solution of sodium oleate and NH4F, stir evenly and evaporate to remove the methanol, then react at 290-300°C under inert gas protection for 60-90 minutes, cool to room temperature, add a precipitant, centrifuge and wash to complete an inert shell coating; repeat the coating operation once to obtain a four-layer core-shell structure upconversion luminescent material.
4. The preparation method according to claim 3, characterized in that: In S1, the molar ratio of ErCl3, TmCl3, sodium oleate and NH4F is 1-x:x:2.5:4, x=0~2%.
5. The preparation method according to claim 3, characterized in that: In S2, the molar ratio of YbCl3, sodium oleate and NH4F is 1:2.5:
4.
6. The preparation method according to claim 3, characterized in that: In S3, the molar ratio of Y(CH3COO)3, sodium oleate and NH4F is 1:2.5:
4.
7. The preparation method according to claim 3, characterized in that: In S1, S2 or S3, the volume ratio of oleic acid to 1-octadecene is 6:
14.
8. The preparation method according to claim 3, characterized in that: In S1, S2 or S3, the concentration of the methanol solution of NH4F is 0.4 mol / L.
9. The preparation method according to claim 3, characterized in that: In S1, S2 or S3, the precipitant is methanol or ethanol.